ERROR ANALYSIS ON ENGLISH CONSONANTS PRONUNCIATION PRODUCED BY SECOND SEMESTER STUDENTS OF STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - WIDYANINGTYAS, ISHARDINI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: Error, Error analysis, Consonant, English consonants. In the process of learning English as a foreign language, many learners face difficulties and produce some errors especially in pronouncing English consonants as well as English vowels. In this study, the writer was interested to analyze the phonological errors made by second semester students of Study Program of English Universitas Brawijaya regarding English consonants. Hence, the main focus of this study was the 24 English consonants. By conducting this study, the writer was able to find: first, the English consonants pronunciation error produced by the second semester students; and second, possible factors that influence their error. In answering the first research problem, the writer used Kelly’s and also Ladefoged et al.’s theories. Meanwhile, in answering the second research problem, the writer used Kenworthy and also Piske et al.’s theories. Moreover, the writer conducted her research using qualitative approach. In collecting the data, the writer firstly recorded the pronunciation of second semester students of Study Program of English Universitas Brawijaya when they read the pronunciation tasks provided. Then, she transcribed their pronunciations.The result showed that the students produced phonological errors in pronouncing thirteen consonants, those are /g/, /h/, /j/, /k/, /v/, /z/, /ʤ/, /ʧ/, /ɵ /, /ð/,/ƞ/, /ʒ/, and /ʃ/. Meanwhile, for the other consonants such as /b/, /d/, /f/, /l/, /m/, /n/, /p/, /r/, /s/, /t/, and /w/ are consonants which are error-free in pronunciation. Additionally, the most troublesome English consonant for the students is /v/. The writer also found 3 causes which give certain effect toward students’ error in pronunciation, those are the interference of L1 into L2, formal instruction, and the amount of L2 use.Based on these results, it can be concluded that the second semester students have not mastered the pronunciation of English language yet because most of them are still influenced by their first language pronunciation system. Finally, the writer suggests the future researchers conduct further research in spoken language since the number of this kind of research is limited. They could continue this study and find more information of students’ weakness in pronouncing English words